Analisis Kualitas Udara CO2 di Permukiman Sekitar Pertambangan PT Vale Kabupaten Luwu Timur - Alfriska Rante; Herawaty Riogilang; Hendra Riogilang (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2025)
This research aims to analyze air quality, particularly the concentration level of carbon dioxide ( in residential areas located around the nickel mining site of PT Vale in East Luwu Regency, covering Towuti, Nuha, and Wasuponda. The focus of this study is related to the impacts of urbanization and increased transportation activities that contribute to global warming. The research methods include calculating carbon dioxide ( emissions originating from transportation activities, human respiration, livestock, and LPG fuel consumption. Additionally, an analysis of the absorption capacity by existing vegetation is also conducted. Primary data were obtained through traffic counting surveys and vegetation surveys, while secondary data were collected from the Central Statistics Agency (BPS) and relevant agencies. The research results show that the total emissions in the residential area around the PT Vale mining site in East Luwu Regency are 67,351.38 tons/year. The existing vegetation can only absorb 5,814.05 tons per year or about 21% of the total emissions. The projected emissions until 2049 show a significant increase, making emissions from transportation the largest contributor, with a total projected emission of 2,123,067 tons per year. Therefore, additional planning for Green Open Spaces (RTH) is needed, with the planting of mango and trembesi trees, as well as the implementation of Roof Gardens to optimize absorption.